2022
DOI: 10.1177/23259671221137357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Posterior Cruciate Ligament Reconstruction Using an All-Inside Technique With and Without Independent Suture Tape Reinforcement

Abstract: Background: Biomechanical studies support the use of suture tape reinforcement for limiting graft elongation and increasing strength in knee ligament reconstructions. Purpose: To compare posterior cruciate ligament (PCL) laxity, complication and reoperation rates, and patient-reported outcomes (PROs) after all-inside single-bundle PCL reconstruction (PCLR) with versus without independent suture tape reinforcement. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective cohort study of consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Even in studies such as Therrien et al that demonstrated similar clinical outcomes in the all-inside single-bundle PCL reconstruction with and without suture tape reinforcement acknowledge that the severity of injuries varied between cohorts being compared. 38 Still, individual case reports have demonstrated the viability of suture augmentation in severe multi-ligament knee injuries, illustrating a clear need for high-quality prospective trials comparing traditional reconstruction with and without suture augmentation. 37,39…”
Section: Posterior Cruciate Ligamentmentioning
confidence: 99%
“…Even in studies such as Therrien et al that demonstrated similar clinical outcomes in the all-inside single-bundle PCL reconstruction with and without suture tape reinforcement acknowledge that the severity of injuries varied between cohorts being compared. 38 Still, individual case reports have demonstrated the viability of suture augmentation in severe multi-ligament knee injuries, illustrating a clear need for high-quality prospective trials comparing traditional reconstruction with and without suture augmentation. 37,39…”
Section: Posterior Cruciate Ligamentmentioning
confidence: 99%